Strategic supplementation of multinutritional blocks for goats (Capra hircus) under an intensive system on the central coast of Peru - Sessarego Dávila, Enmanuel Alexander (2025)
The objective of this study was to evaluate the effect of supplementation of multi nutritional blocks (MNB) for growing goats on their productive and economic performance in an intensive system, on the central Peruvian coast. For this, 51 Saanen goats at two months of age and 9.7±1.4kg live weight on average were randomly distributed in three treatments: T0 = control; T1 = MNB supplementation with 24% crude protein (CP), and T2 = MNB supplementation with 29% CP, for a period of two months. Initial live weight (ILW, kg), final live weight (FLW, kg), weight gain (WG, kg), survival rate (SR, %) and economic retribution (ER, S/) were evaluated, using SPSS v. 27. Values of 16.17±1.65 and 6.52±1.44kg were obtained for FLW and WG, respectively, and the SR was 100% for all groups. On the other hand, MNB supplementation had a highly significant effect (p = 0.000) on FLW and WG, and a higher SR was observed when MNB was supplied with 24% CP. In conclusion, MNB supplementation with 24% CP for growing goats, under an intensive production system, significantly improves their productive performance and would achieve a higher economic return.